Effect of Problem-Based Learning Approach on Elementary School Students' Critical Thinking Skills in Mathematics Learning - Azmil Hasan Lubis (Journal of Indonesian Primary School, 2025)
Critical thinking skills are one aspect that every student must possess in mathematics learning, especially in elementary schools. This study aims to examine the impact of using a problem-based learning approach on students' critical thinking skills in mathematics learning. This research is a quantitative research with an experimental research type. The experimental design used in this study is a quasi-experimental study involving one experimental class and one control class. The population of this study was elementary school students. The sampling technique used was cluster random sampling. Data were obtained using test techniques, then analyzed using descriptive and inferential statistical techniques. The results of the study indicate that the problem-based learning approach can have a significant effect on elementary school students' critical thinking skills in mathematics learning. This is evidenced by the results of descriptive statistical tests which show that the experimental class obtained an average score of 87.93 and the control class 65.35, meaning there is a gap of 25.68%. The t-test results also show that the significance value is 0.00 (<0.05), which means there is a difference in the critical thinking skills of students who participated in the mathematics learning process using the problem-based learning approach and those who did not. Based on these results, it is proven that the problem-based learning approach can be used as an alternative to optimize the critical thinking skills of elementary school students in mathematics learning.